Tracking the eye of the beholder: is explanation subjective?. Issue 2 (17th February 2021) - Stewart, Andrew J.; Singmann, Henrik; Haigh, Matthew; Wood, Jeffrey S.; Douven, Igor
ABSTRACT: There is much recent evidence showing that explanation is central to various cognitive processes. On the other hand, philosophers have argued that the notions of explanation and explanation quality are too subjective for explanation to play any role in science: what may be an adequate explanation for one person may fail to be so for another. We compare the results of a study tasking participants with rating explanation quality with those of an eye-tracking study, finding that ratings of explanation quality from participants in the former study were strongly predictive of the ease with which participants in the latter study processed text fragments presenting the same explanations that were used in the rating study. This finding undermines the thought that explanation is only in the eye of the beholder.